PERANCANGAN SISTEM PAKAR UNTUK MENILAI KINERJA IRIGASI - Hoerudin Hoerudin; Budi Santosa (Rekayasa Sipil, 2022)
Irrigation is a supporting infrastructure for water distribution in agriculture. Its role is vital, especially for agricultural areas which are not rain-fed, meaning that to irrigate agricultural areas the irrigation infrastructure is needed. It is important for all parties involved in agriculture and irrigation management institutions to find out and ensure the condition and performance of an irrigation network, whether its function is still as planned or even vice versa. So far, the performance evaluation of irrigation networks is still carried out conventionally and only reaches a form of Maintenance Operation report, not specific to its performance. So based on these conditions, this research will build an expert system that can be used to assess the performance of irrigation networks. The design begins by determining the logic of assessment that will be used as a way of thinking from the expert system that will be built. The indicators used by the system to assess irrigation performance are as stated in the regulation of the Ministry of Public Works and Public Housing No. 12 of 2015. After designing the expert system, the next step is to simulate it using the data available in the operation and maintenance reports of some irrigation networks that are used as samples. Then the simulation results are analyzed so that it can be known whether the system can work as planned or not. The system simulation results show a mismatch between the two indicators namely the performance of infrastructure and water services. While other assessment indicators have logical results.